A multidisciplinary approach to quantum field theory. - Ogilvie, Michael, 1953- (IOP (Series). Release 22., 2022)
This book covers quantum field theory at an introductory level appropriate for graduate students in physics. The first volume aims to allow students to begin their research in fields using quantum field theory, such as particle physics, nuclear physics, cosmology and astrophysics and condensed matter physics. The key areas the book explores include free (noninteracting) fields, field quantization, interacting fields, Feynman diagrams, scattering, cross sections and decay rates; renormalization; symmetry, symmetry breaking and Goldstone bosons. Graduate students studying particle, nuclear, and condensed matter physics are the key audience for this volume. It will also be useful to researchers looking for a modern overview of quantum field theory.